Maimed bodies in George R.R. Martin's A song of ice and fire - Goodenough, Amy Caroline (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
George R.R. Martin's fantasy series, A Song of Ice and Fire, has joined franchises like Harry Potter and The Lord of the Rings at the forefront of popular culture. Unlike other popular fantasy franchises, however, Song is notably 'gritty' - inspired as much by the realism of historical fiction as it is by its fantastical predecessors. The novels focus on a massive struggle for power, and that struggle is a famously bloody one: the violence of the novel's medieval-inspired world and of medieval warfare, is placed front and center. This thesis argues that Song portrays this excessive violence with a view to more than mere sensation. The body is central to Martin's text, and since power is the object of Martin's characters, he depicts the way in which power interacts with the body with sophistication. The use of capital and corporal punishment is foregrounded frequently in the text, and presented as central to the process of ruling, but horrifying in its potential for injustice. For all that these acts of maiming - public execution, public torture - may be presented as ceremonies of justice, Martin makes it evident that they are in fact rituals of power. The spectacular display of maimed bodies occurs frequently - so frequently that it is clearly ordinary to Martin's characters - and nearly always with a view to creating a perception of power. Heads are spiked on castle walls, gibbets hung in town squares, and slaves crucified on road-signs, and these all speak not of the criminality of the victims, but of the power of those doing the punishing. While such displays may be successful, they usually signal weakness to the reader: Martin writes numerous characters whose acts of violence come as misplaced reactions to their own vulnerability. This dynamic comes to the fore most powerfully in the absurd performances of violence by Theon Greyjoy, and, later, in his torture by Ramsay Bolton.
Keywords: Martin, George R. R. -- Song of ice and fire; Violence in literature; Fantasy fiction -- History and criticism